40 Days vs. 120 Days - Rahmat Hidayat; Muhammad Iqbal Irham; Muhammad Faisal Hamdani (Waraqat: Jurnal Ilmu-Ilmu Keislaman, 2025)
One of the consequences of rape is unwanted pregnancy, which may lead to both psychological and physical distress, often resulting in the desire to undergo an abortion. According to the 2023 Indonesian Penal Code (KUHP) and the opinion of the Hanafi school of thought, abortion is permissible before the pregnancy reaches 14 weeks or 120 days. In contrast, under the 2009 Health Law and the Shafi'i school of thought, abortion is only allowed before 6 weeks or 40 days of gestation. This discrepancy calls for further examination to determine the most appropriate legal threshold for abortion in rape cases, from both the perspectives of positive law and Islamic jurisprudence. This study employs a qualitative method with a comparative approach, utilizing literature review and document analysis of statutory law, classical Islamic legal texts, and relevant medical literature. It also applies the principle of hifz al-nafs (protection of life) as a normative foundation. The findings reveal that the 2023 revision of the Penal Code, which extends the permissible period for abortion from 6 to 14 weeks, aligns with the majority of Islamic scholars who permit abortion before 120 days of gestation. Nonetheless, abortion before 40 days is preferable to avoid legal controversy and reduce medical risks and psychological trauma. This study recommends harmonizing national laws, medical ethics, and Islamic legal principles to ensure substantive justice and optimal protection for victims of sexual violence